Special'naja fiziceskaja podgotovka v vidach sportivnych edinoborstv - Pankov, V. A.; Akopjan, A. O. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The analysis of scientific researches on the problem of treatment of physical qualities of athletes was shown, that recently the attention of specialists in the area of sports is directed on the studying and the selection of the most effective means and methods of physical training. It is showing the increased requirements to the functional systems of an organism of the athletes which abilities determine the success of the competitive activity.